Internal marketing and job satisfaction in hotels in Via Costeira, Natal, Brazil - Marques,Carlos Peixeira (2018)
Organisations currently face multifaceted challenges, such as increasing productivity and coping with the pressure to manage human resources efficiently and effectively. This involves management practices focused on training and keeping the best employees. In this context, the present study sought to assess the impact of internal marketing practices in hotels of superior quality in a city in Brazils Northeast Region on internal customers commitment and satisfaction. Measures of internal market orientation, organisational commitment and job satisfaction were collected for a sample of 138 intermediate/lower managers from four hotels. The results from a structural equation model confirm the positive influence of internal marketing on organisational commitment and job satisfaction but fail to confirm the expected relationship between commitment and satisfaction.